Scaling up of PCR-based surveillance of bacterial meningitis in the African meningitis belt: indisputable benefits of multiplex PCR assay in Niger. - (:unkn) unknown (My University, 2006)
The absence of reliable laboratories for culture of Neisseria meningitidis, Haemophilus influenzae and Streptococcus pneumoniae, the three main causes of bacterial meningitis in Africa, hampers microbiological surveillance in these countries. To compensate for this situation in Niger, a multiplex single-tube PCR method has been implemented at a central level to test cerebrospinal fluid (CSF) samples. The overall confirmation rate for PCR (N=3791) was 40.8% compared with 16.0% for culture (N=945) (P<10(-6)). Among 850 CSF specimens tested by both methods, the overall confirmation rate was 29.4% for PCR and 16.4% for culture (P<10(-8)). PCR was also efficient for the CSF specimens stored in Trans-isolate medium. In conclusion, PCR assay is currently a key tool in Africa to improve microbiological surveillance of bacterial meningitis.
Keywords: African Research